ON THE SITUATED SOCIO-CULTURAL MEANING OF BENEFACTIVES IN BALINESE - Desak Putu Eka Pratiwi; I Wayan Arka; Asako Shiohara (Masyarakat Linguistik Indonesia, 2018)
This paper discusses a preliminary corpus-based study of benefactives in Balinese, from a socio-cognitive theory of situated socio-cultural meaning (cf. Langlotz 2015, Danielle and Evans 2017). It is part of larger corpus-based research on parallel texts in the international SCOPIC (Social Cognition Parallax Interview Corpus) project (http://hdl.handle.net/10125/24742). Benefactive constructions are defined as those expressing states of affairs (SoA) hold to someone’s advantage (Kittilä and Zúñiga 2010). The notion of '(someone's) advantage' in Balinese benefactive meaning is tightly embedded in Balinese cultural worlds, having complex positive social meanings in which concepts such as 'self', 'reciprocity', 'in-.out-group', and spiritual rewards are central. The socio-cultural worlds are evidently reflected the speech level system in Balinese. There are different forms with fine-grained social meanings such as three words for 'give' in Balinese depending on the relative social relations of event and/or speech participants. An incorrect choice of linguistic device would lead to incorrect social indexing; hence socially unacceptable or inappropriate, not giving rise to the intended positive benefactive meaning. Our findings show that benefactive meaning is expressible through different means (lexical, morphological, and analytical/constructional). Surprisingly, the lexical benefactive 'give' is 100% expressed through the verb baang in our Balinese SCOPIC corpus, suggesting that the corpus is rather skewed towards the common (or low) register.